Sistem Pakar Mendiagnosa Penyakit Keputihan Pada Wanita Dengan Metode Teorema Bayes - Christina Simanjuntak; Fristi Riandari (Program Studi Teknik Informatika, Fakultas Teknik. Universitas Serambi Mekkah, 2021)
Leucorrhoea is a discharge other than blood from the vaginal canal, if abnormal vaginal discharge is left untreated, as a result the infection can spread, enter the uterus, fallopian tubes, and can infect the ovaries. The application of an expert system in the health sector will greatly assist in survival someone. Expert systems can help diagnose a type of disease based on their own symptoms quickly and precisely. An expert system that is designed as a tool to diagnose the type of leucorrhoea, especially in women who experience vaginal discharge, but often they feel able to recognize themselves that they are suffering from vaginal discharge without feeling the need to go to a doctor for a more detailed examination, and only treat themselves with medication. Free-sale vaginal discharge medication. This expert system will display a selection of symptoms that can be selected by the user, then get the final result with the Bayes theorem method by providing a diagnosis result in the form of a probability value for the emergence of each type of disease and solution. Expert system applications are built on a web basis using HTML, PHP, CSS using the mysql database.